Experimental study of chemical-etched high-power cladding mode stripping device toward high attenuation. (July 2023) - Liu, Yu; Wu, Wenjie; Li, Yuwei; Li, Yue; Huang, Shan; Tao, Rumao; Lin, Honghuan; Wang, Jianjun
Highlights: Cladding mode stripper toward high power and high attenuation is investigated. Surface roughen is effective at the first few centimeters, but not after. Cladding reduction can greatly improve the attenuation, but induce localized heat. Fabrication of combined structure with tailorable light-strip behavior is presented. Experimental result of > 2-kW stripped power and 39-dB attenuation is demonstrated. Abstract: Fiber cladding mode stripping device with high-power high-attenuation stripping capability and negligible perturbation to signal light has been developed by employing Teflon-capillary segmental-etching fabrication method. By using different etchant solutions, surface roughening and cladding reducing structures can be obtained. The influence of the roughened length on the attenuation of cladding power has been studied experimentally, showing that roughened surface strips cladding light well at length below 5 cm, but becomes less effective beyond that. The impact of the cladding reduction has also been investigated, indicating that reduced cladding can help deplete the cladding light effectively, and the attenuation is able to be improved from 23.0 dB to 43.2 dB by etching the cladding diameter from 400 μm to 50 μm. By combining the roughened surface and reduced cladding structures, cladding mode stripper with 7 °C/kW of temperature rising rate on the etched area has been made, and stripped power up to 2.1 kW at 39 dB of attenuation has been demonstrated, with the device length merely 16 cm. The maximum temperature on the device housing at full operation power for the case water flux being 3.1 L/min and 5.6 L/min is 67 °C and 50 °C, respectively. To the best of our knowledge, this is the first report of >2-kW power cladding mode stripping device with 39-dB attenuation. All results indicate the effectiveness of the proposed fabrication technique to make cladding mode stripping device for high power and superior beam quality fiber laser systems.